2010
DOI: 10.3892/or_00001023
|View full text |Cite
|
Sign up to set email alerts
|

HPV-16 E6 upregulation of DNMT1 through repression of tumor suppressor p53

Abstract: Abstract. The HPV-16 early proteins E6 and E7 are considered to function as oncoproteins in cervical cancer. DNA methyltransferase 1 (DNMT1) is one of the enzymes involved in epigenetic silencing of tumor suppressor genes. In the present study, the functional role and regulation of DNMT1 in HPV-16 E6 associated cervical cancer development were examined. Knockdown of E6 in HPV-16 positive human cervical carcinoma SiHa and CaSki cells led to the increase in p53, repression of DNMT1 protein and promoter activity.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…Au Yeung CL et al proved that HPV-16 E6 upregulation DNMT1 through repression of tumor suppressor p53. 33 It has been reported that high expression of DNMT1can increased radiosensitivity. 34 In this study, the expression of DNMT1 in HPV (-) cells was lower than HPV (+) cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Au Yeung CL et al proved that HPV-16 E6 upregulation DNMT1 through repression of tumor suppressor p53. 33 It has been reported that high expression of DNMT1can increased radiosensitivity. 34 In this study, the expression of DNMT1 in HPV (-) cells was lower than HPV (+) cells.…”
Section: Discussionmentioning
confidence: 99%
“…The expression level of DNMT1 and methylation level are related to the expression of E6. 33 For many years, SMG1 has been known as a critical component of an evolutionarily conserved mRNA surveillance mechanism. [35][36][37] It was later discovered to be involved in the maintenance of genome integrity via genotoxic stress response pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, HPV infection has profound effects upon the host methylome: 8000 and 10 000 genes were demonstrated to have altered DNA methylation levels, either increased or decreased, in primary keratinocytes harbouring episomal HPV16 and HPV18 genomes, respectively [ 171 ]. E6 indirectly increases DNMT1 expression through the degradation of p53 [ 172 ]. p53 negatively regulates DNMT1 expression by binding in concert with Sp1 to the DNMT1 promoter but in the absence of p53, Sp1 acts to enhance DNMT1 expression [ 173 ].…”
Section: The E6 Oncoproteinmentioning
confidence: 99%
“…DNA methyltransferases (DNMTs) are mammalian enzymes responsible for maintaining CpG methylation, and DNMT1 can be activated by both E6 and E7 of hrHPV (Verlaat et al, 2018). E6 can upregulate DNMT1 via p53, and E7 can directly bind to and activate DNMT1 (Burgers et al, 2007; Au Yeung et al, 2010). Conversely, silencing of E6 and E7 could reduce DNA methylation levels and restore the transformed phenotype in CC cells (Rampias et al, 2009; Li et al, 2015b; Verlaat et al, 2018).…”
Section: Discussionmentioning
confidence: 99%